2020
DOI: 10.1371/journal.pone.0219633
|View full text |Cite
|
Sign up to set email alerts
|

Contributions to human breast milk microbiome and enteromammary transfer of Bifidobacterium breve

Abstract: Increasing evidence supports the importance of the breast milk microbiome in seeding the infant gut. However, the origin of bacteria in milk and the process of milk microbe-mediated seeding of infant intestine need further elucidation. Presumed sources of bacteria in milk include locations of mother-infant and mother-environment interactions. We investigate the role of mother-infant interaction on breast milk microbes. Shotgun metagenomics and 16S rRNA gene sequencing identified milk microbes of mother-infant … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(119 citation statements)
references
References 34 publications
9
92
0
Order By: Relevance
“…More recently, Kordy et al used shotgun metagenomics to identify a distinct Bifidobacterium breve strain in the mother's rectum, breast milk, and infant gut. Therefore, this study may support the hypothesis of entero-mammary pathway, allowing for the transport of Bifidobacteriium breve from maternal gut to the mammary gland [232].…”
Section: Origins Of Milk Microbiomesupporting
confidence: 82%
“…More recently, Kordy et al used shotgun metagenomics to identify a distinct Bifidobacterium breve strain in the mother's rectum, breast milk, and infant gut. Therefore, this study may support the hypothesis of entero-mammary pathway, allowing for the transport of Bifidobacteriium breve from maternal gut to the mammary gland [232].…”
Section: Origins Of Milk Microbiomesupporting
confidence: 82%
“…Our results confirm that feeding type also have a significant influence on gut microbiome richness, diversity and bacterial load 3133 . Exclusive or partial feeding with mother’s own milk tended to associate with high bacterial load, which is supported by evidence that breast milk harbors maternal-originating bacteria, as well as nutritional components (prebiotics) that support bacterial proliferation in the intestinal tract 34,35 . Interestingly, formula-fed infants had comparable levels of richness, diversity and bacterial load as mother’s milk.…”
Section: Discussionmentioning
confidence: 83%
“…It has been suggested that commensal bacteria from maternal skin (such as Staphylococcus, Corynebacterium, and Cutibacterium) or the infant's mouth (such as Streptococcus) can enter the mammary duct during breastfeeding [32]. Another hypothesis is that the maternal gut bacteria enter the mammary glands through the entero-mammary pathway, which would require the cells to penetrate the intestinal epithelium and reach the mammary glands through the bloodstream [33][34][35]. The observation that anaerobic bacteria such as Bacteroides, Bifidobacterium, Parabacteroides, and Clostridium that are not found on the skin are detected and shared between HBM and infant feces supports this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…We especially highlighted Bifidobacterium, as the gut microbiota of infant feces usually exhibits high abundance of this bacterium, with exclusively breastfeeding infants in particular exhibiting relatively abundant Bifidobacterium in the feces [36,37]. [35,36]. Several lines of evidence suggest that the relative level of Bifidobacterium abundance correlates with the development of disease or immunity.…”
Section: Discussionmentioning
confidence: 99%